The degrees and configurations of mesial canal curvatures of mandibular first molars - (:unkn) unknown (ELSEVIER SCIENCE INC, 1997)
The objective of this study was to determine the frequency, degree of curvature, and the configuration of mesiobuccal and mesiolingual root canals of mandibular first molars. The degree of curvature and configuration of root canals creates some technical difficulties to the clinician during biomechanical preparation. Therefore this knowledge is essential for successful endodontic therapy. Six hundred and ninety-seven freshly extracted mandibular first molars were used in this study. After introducing 0.8 to 15 K reamers into the mesial root canals, the teeth were radiographed in buccolingual (clinical) and mesiodistal (proximal) directions. All samples showed curvatures at varying degrees in both views. There was a significant correlation between the degree of primary curvature of mesiobuccal and mesiolingual canals in clinical directions for total samples. When the primary curvature values of the mesial root canals were evaluated in Vertucci classification, the mesiobuccal and mesiolingual canals in Vertucci type VI were found as significantly correlated (r = 0.7173, p < 0.05). A significant correlation was seen between the secondary curvature values of clinical and proximal views of mesiolingual canal in Vertucci type VI (r = 0.9891, p < 0.05). The secondary curvature values in the clinical views of mesiobuccal and mesiolingual canals were found as significantly correlated in Vertucci type II.
Keywords: CURVED ROOT CANALS; INSTRUMENTATION; MASTER